Hepatic Lipodystrophy in Galloway Calves. (May 2017) - Wieland, M.; Mann, S.; Hafner-Marx, A.; Ignatius, A.; Metzner, M.
Hepatic lipodystrophy in Galloway calves is a fatal liver disease affecting a small proportion of the Galloway breed described in different parts of Europe and North America during the past decades. The clinical findings include a diversity of neurological signs. Clinical pathology findings frequently indicate hepatobiliary disease. Postmortem examination reveals an enlarged, pale yellow, and firm liver. Histologic lesions include hepatic fibrosis, hepatic lipidosis, and bile duct hyperplasia. To date, the etiopathogenesis remains obscure. Infectious causes, intoxications, and a hereditary origin have been considered. We describe hepatic lipodystrophy in Galloway calves from an extensively farmed cow-calf operation in southern Germany. Main clinical findings in 6 calves were consistent with hepatic encephalopathy. Clinical pathology findings in 5 of 6 tested animals revealed increased concentration of total bilirubin (maximum value [MV], 54 μmol/l; reference range [RR], <8.5 μmol/l), direct bilirubin (MV, 20 μmol/l; RR, <3.4 μmol/l), increased activity of gamma glutamyl transferase (MV, 162 U/l; RR, <36 U/l) and glutamate dehydrogenase (MV, 420 U/l; RR, <16 U/l). In addition, activity of glutathione peroxidase was decreased in all tested ( n = 5) animals (MV, 61 U/g hemoglobin [Hb]; RR, >250 U/g Hb). Postmortem examination in 6 calves revealed a firm, diffusely enlarged yellow liver with a finely nodular surface. Histologic lesions included hepatic fibrosis, hepatic lipidosis, and bile duct hyperplasia. Our findings add to the existing data on hepatic lipodystrophy in the Galloway breed and outline a protocol to aid in the diagnosis of this disorder.